Incisional Hernia Case Management in a Local Cat - Palagan Senopati Sewoyo; Made Santi Purwitasari; Pramita Rabiulfa; I Wayan Wirata (Universitas Airlangga, 2023)
Background: An incisional hernia is a condition where the sutures on the abdominal wall rupture while the sutures on the skin remain intact. This causes abdominal viscera to protrude through the surgical incision hole, resulting in a visible lump. Purpose: Literature reports regarding incisional hernias in animals are very rarely reported; therefore, this case report aims to provide information about incisional hernias. Case: An eight month old female cat weighing 1.7 kg was presented at the Veterinary Surgery Laboratory, Veterinary Medical Faculty of Udayana University, with clinical signs of a lump on the ventral side of the abdomen, with visible stitch scars in the lump area. Upon pressing the lump, it could be reinserted, leading to a diagnosis of incisional hernia. Case Management: The cat underwent herniorrhaphy to return the visceral organs to the abdominal cavity and close the hernial opening. Post-operative care included administering cefotaxime 20 mg/kg BW intravenously twice a day for three days, followed by cefixime 5 mg/kg BW orally twice a day for four days, and non-steroidal anti-inflammatory drugs tolfenamic acid of 4 mg/kg BW subcutaneously once a day for three days. The wound area was covered with 1% framycetin sulfate tulle gauze (Daryant-Tulle®), and the stitches were removed on the 14th postoperative day. Conclusion: The wound appears dry, with well-approximated edges and no visible protrusion. It can be concluded that treatment with herniorrhaphy in this case was successful.